INTERAKSI SOSIAL ASOSIATIF ANTAR ANGGOTA KOMUNITAS STAND UP COMEDY DI KOTA PONTIANAK - Nur, Muhammad Fajriadi; Zakso, Amrazi; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The title of this research is "Associative social interaction intercommunity members stand up comedy in Pontianak city.â€ The general problem of this research is how associative social interaction intercommunity members stand up comedy in Pontianak city? The problem is how associative social interaction in cooperation and in accommodation intercommunity members? The purpose of research is for to know how associative social interaction intercommunity members? This study uses a descriptive qualitative approach. Data collection techniques using observation, interviews, and documentation studies. The research analysis was presented in a qualitative descriptive manner using 4 informants, consisting of 1 leader and 3 members who actively participated in community activities. The results showed that associative social interactions in the form of cooperation and accomomodation intercommunity members had gone well. This is seen when in daily life members work together to make stand up comedy material and help in preparing the openmic stage,and mutual assistance to prepare the equipment for display andin their daily lives, members avoid conflicts with mutual understanding if there are disputes and conduct simulations in advance to avoid offense or material that isnâ€™t suitable for display. Keywords: Interaction, Associative, Stand up Comedy